2003
DOI: 10.1023/b:apih.0000036413.87440.83
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Use of Mechanical Restraints and Locked Seclusion

Abstract: This article describes attempts by an inpatient unit, treating adolescents with developmental delays and with severe psychiatric disturbances, to reduce its use of physical restraints. This restraint reduction process involved two phases: (1) assessment and (2) systems intervention. The assessment phase consisted of extensive observations of staff response to patient crises, staff interviews, patient interviews, and the development of a data-tracking system for restraint and seclusion (R/S) usage. Multiple con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 11 publications
0
40
0
5
Order By: Relevance
“…The development of trusting and respectful interactions between patients and staff as a result of engaging in such activities is a valuable asset for decreasing the use restraint and seclusion, and in promoting harmony and collaboration in secure inpatient settings (Schreiner et al 2004). Circuit cricket was the most popular game identified by participants, and this team sport also demonstrates how meaningful activities can bring together people from diverse cultural backgrounds and language groups to enjoy physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…The development of trusting and respectful interactions between patients and staff as a result of engaging in such activities is a valuable asset for decreasing the use restraint and seclusion, and in promoting harmony and collaboration in secure inpatient settings (Schreiner et al 2004). Circuit cricket was the most popular game identified by participants, and this team sport also demonstrates how meaningful activities can bring together people from diverse cultural backgrounds and language groups to enjoy physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…17,[22][23][24] Rates of restraint and seclusion may be affected by differences in hospital characteristics independent of patient population, 25 including geographical location, 25,26 size, 15 and patient-to-staff ratio. 27 Several authors have described efforts to reduce rates of restraint and seclusion, 10,16,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] mostly in urban psychiatric hospitals, in adult 10,[28][29][30][31][32][33][39][40][41][42] or adolescent [34][35][36][37][38] units, or in psychiatric emergency departments. 33 One common component of such programs is improved staff education that includes addressing opinions and beliefs about use of restraint and seclusion, providing information about regulations and hospital policies, and suggesting alternative methods for de-escalating patient behaviors.…”
mentioning
confidence: 99%
“…33 One common component of such programs is improved staff education that includes addressing opinions and beliefs about use of restraint and seclusion, providing information about regulations and hospital policies, and suggesting alternative methods for de-escalating patient behaviors. [28][29][30]35,36,39,41 In a study at one hospital, Klinge demonstrated that staff had a range of opinions regarding indications for restraint and seclusion, 43 which suggests that staff education could improve uniformity of beliefs and clinical practice. Debriefing of staff after events 34,39 can be both an educational opportunity and a way for hospital leaders to learn more about the context and frequency of restraint and seclusion use.…”
mentioning
confidence: 99%
See 2 more Smart Citations